The Pluralist Imperative: Reforming the International Criminal Court's Complementarity Principle through a CLP Lens - Berebon, Charles (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
The International Criminal Court (ICC), governed by the state-centric complementarity principle in Article 17 of the Rome Statute, faces a persistent legitimacy crisis. Its “unwilling or unable” test, designed to adjudicate between national and international jurisdiction, systematically marginalizes non-state, community-based justice mechanisms (CBJMs). This paper argues that this legal centralist approach delegitimizes vital local practices like Uganda’s matu oput and Rwanda’s gacaca, undermining the ICC’s efficacy and moral authority. Applying the tenets of Community Legal Pluralism (CLP), this article offers a critical doctrinal analysis of ICC jurisprudence and a comparative study of its application in contexts like Colombia and Uganda. It posits that CLP—with its emphasis on collective well-being and participatory governance—provides the necessary theoretical lens to reform the complementarity principle. The paper proposes a concrete “pluralist complementarity” framework, outlining specific criteria (e.g., procedural fairness, human rights safeguards, and community legitimacy) for the Office of the Prosecutor to assess CBJMs. Furthermore, it recommends procedural reforms to formally integrate participatory input from traditional justice authorities during preliminary examinations and trial phases. By moving CLP from theoretical critique to actionable institutional reform, this paper provides a blueprint for transforming the ICC into a facilitator of “glocalized” justice, thereby enhancing its legitimacy and effectiveness in the pluralistic global order.